The Legal Implications of Establishing Land Bank As An Entity Authorized to Manage Land - aini, Nur’Aini; Koeswahyono, Imam; Wisnuwardhani , Diah Ayu (Universitas Islam Malang, 2024)
Land is an important resource that controls the livelihoods of many people. Land has social, economic, cultural and even spiritual value. The presence of the state based on Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) is to regulate land allocation in a fair manner. This is also stated in the UUPA. However, since the presence of the Land Bank, it has actually triggered problems, especially in the normative order, in this case what is highlighted is the conflict of norms. Leads to two problem formulations. First, what is the essence of the Land Bank's regulation as a body that is given the authority to manage land? Second, what are the legal implications of regulating the Land Bank as a body given the authority to manage land? Using normative legal research methods, with a statutory statute approach and theoretical approach. The resulting analysis shows that the current Land Bank regulations in Law no. 6 / 2023 in conjunction with PP No. 64 / 2021, turns out to have closer economic nuances. This also shows a lack of harmony with Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, UUPA and the objectives of agrarian reform. This regulation has legal implications, both philosophically, normatively and sociologically. Therefore, it is necessary to evaluate and reorganize Land Bank regulations in Indonesia so that they provide legal certainty and more equitable use.